SYNTHESIS AND INVESTIGATION OF OPTICAL PROPERTIES OF THIN FILMS OF TiO2, OBTAINED WITH THE MEDIA OF DIFFERENT ALCOHOLS - Alexander Kravtsov; Andrew Blinov; Svyatoslav Krandievskiy; Artem Rusanov (Вестник Северо-Кавказского федерального университета)
Urgency of the work is due to demandfor new efficient and cheaper materials for electronics, optics and solar energy and the necessity of studying of their properties. The developed technique allows obtaining of thin films of titanium dioxide. The nature of the alcohol used as a solvent has an insignificant effect on the optical properties of the films, however, affects on the thickness offilms obtained by deposition on a rotating substrate. It can indirectly indicate by the displacement of the interference fringe on the the transmission spectra. During calcination of the samples at 400 ° C transparency of TiO2 films decreases. IR spectroscopy shows that titanium aquacomplexes decomposition and desorption takes place with calcination. Also occures desorption of the bound water and the decomposition of chlorine-containing complexes formed in the process ofproducing films of TiO from the titanium chloride.